An Overview of Manav Nyayashastra (Nyayavikashini) - Joshi, Yagya Raj (KVM Research Journal, 2025)
Manav Nyaya Shastra also known as Nyayavikashini, holds significant historical importance as it established Nepal’s first unified criminal justice system. King Jayasthiti Malla endeavored to promulgate this code of law to curb the escalating anarchy caused by legal multiplicity. Enacted in 1436 B.S./1380 A.D., it stands as Nepal’s very first codified law, comprising seventeen parts and written in Sanskrit, Newari, and Maithili languages. This comprehensive code addresses four primary areas of law: Griha Nirnaya (Law related to housing), Kshetra Nirnaya (Law related to land management), Jata Nirnaya (Law related to the caste system), Nyayavikashini/Manav Nyaya Shastra (Law related to the administration of justice). The Manav Nyaya Shastra is currently preserved in the Archaeological Department of Nepal.